Peningkatan Hasil Belajar Matematika melalui Penerapan Model Pembelajaran PBL (Project Based Learning) pada Siswa Kelas IVA SDN 48 Cakranegara - Fatmawati, Fatmawati; Nurhayati, Nurhayati (Lembaga Yasin AlSys, 2023)
This research aims to improve Mathematics learning outcomes through the application of the PBL (Project Based Learning) learning model for class IV students at SDN 48 Cakranegara for the 2022/2023 academic year. This type of research is classroom action research (PTK) which is carried out in 2 cycles consisting of planning, action implementation, observation, evaluation and reflection stages. Each cycle consists of one meeting. The results of this research show an increase from cycle to cycle. In cycle I, students' Classical Completeness reached 73% with teacher activity in the very good category and student activity in the quite active category. In cycle II, students' calculus completion reached 88.4% with teacher activity being in the very good category and student activity being in the very active category, this means that Classroom Action Research (PTK) has met the indicators to be achieved. Therefore, based on the research results, it can be concluded that the implementation of the PBL (Project Based Learning) learning model in class IVA students at SDN 48 Cakranegara for the 2022/2023 academic year.